Gambaran Profil Glukosa Darah Puasa dan 2 Jam Post Prandial Pada Lansia di Kelurahan Kenanga Kecamatan Sungailiat - Tonny Loho; Martina Rentauli Sihombing; Netalia Netalia (Jurnal MedScientiae, 2022)
Elderly is a final stage of the human life span which is characterized by physical changes and decreased body functions both anatomically, physiologically and biochemically. The purpose of this study was to describe the profile of GDP and G2PP in the elderly in Kenanga Village, Sungailiat District. In this research, the method used is descriptive research using cross sectional technique. In this study, researchers used primary data by taking capillary blood samples from the respondent's fingers which were then measured using an easy touch glucometer. The sampling technique in this study used a non-probability purposive sampling technique with the number of samples that met the inclusion criteria as many as 42 people. In this study 47.6% of the elderly had normal blood glucose levels, 26.2% of the elderly were prediabetes and 26.2% of the elderly were diabetic. Based age, the elderly aged 60-64 years found 11.9% of the elderly with diabetes, the elderly aged 65-69 years as many as 7.1% and the elderly aged 70-74 years as much as 7.1%. 16.7% and 9.5% men who suffer from diabetes. That the prevalence of diabetes and prediabetes in Kenanga Village, Sungailiat District is not more than 50% of the existing elderly population.